Unusual assemblage of conulariids (Cnidaria, Scyphozoa) from the Taddrist Formation (Middle Ordovician, Darriwilian) of southern Morocco. (July 2022) - Van Iten, Heyo; Gutiérrez-Marco, Juan Carlos; Cournoyer, Mario E.
Abstract: Silty noduliferous shales in the lower part of the Middle Ordovician (late Darriwilian 2) Taddrist Formation in the central Moroccan Anti-Atlas contain a unique assemblage of conulariids consisting of one species each of Archaeoconularia Bouček, 1939, Glyptoconularia Sinclair, 1952, and Pseudoconularia Bouček, 1939 . Glyptoconularia antiatlasica new species, currently represented by a single three-dimensional specimen, is the first member of this extremely rare, highly autapomorphic genus to be described from outside of cratonic North America as well as the first Glyptoconularia from the Middle Ordovician. Pseudoconularia cf. P . grandissima (Barrande, 1867 ) and Archaeoconularia cf. A . exquisita (Barrande, 1867 ) most closely resemble species previously described from Middle and Upper Ordovician strata in the Prague Basin (Czech Republic), then located adjacent to North Africa. Anaconularia anomala (Barrande, 1867 ), previously known from the Upper Ordovician (Sandbian) Libeň and Letná formations in the Prague Basin, is documented for the first time from the Upper Ordovician (Katian) Upper Tioririne Formation of Morocco. In addition to extending the known stratigraphical and paleogeographical ranges of these conulariids, results of the present investigation add to the list of invertebrate taxa that appear to have originated during Early or Mid-Ordovician times in peri-Gondwana or south-polar Gondwana, and then migrated to the eastern margin of Laurentia, arriving there along with other cool-water taxa during the Sandbian-Katian transition. UUID: http://zoobank.org/9ea5051b-cff5-4911-861a-531db4f45883